Program planning from Ralph Tyler's and Malcom Knowles' point of view / Syed Jamal Abdul Nasir Syed Mohamad - Syed Mohamad, Syed Jamal Abdul Nasir (Institute of Education Development (InED), 2007)
This paper discusses the views of Ralph Tyler and Malcom Knowles on Program Planning. Tyler, the founder of classical point of view proposed four basic principles in planning a program which are define objectives, preferably in behavior terms; identify learning experience that will meet these objectives; organize the learning experience into a plan that has scope and sequence and evaluate the outcomes. On the other hand, Knowles who introduced the concept of Andragogy proposed seven basic principles that are establishment of a climate conducive to adult learning; creation of an organizational structure for participative planning; diagnosis of needs for learning; formulation of direction or learning (objectives); development of a design of activities; operation of the activities; and rediagnosis of needs for learning (evaluation). Similarities and differences are found between these two views but they share the same objective which is to enhance better learning outcome.